Bilateral Multiligamentous Knee Injuries: A Case Report and Technique Review - Malynda S. Messer; Brendan Southam; Brian M. Grawe (Case Reports in Orthopedics)
Bilateral knee dislocations are rare musculoskeletal injuries. We report a case of a patient who sustained traumatic bilateral knee dislocations resulting in multiligamentous injuries to both knees. The patient subsequently underwent acute ligamentous reconstructions of both knees performed at 2 weeks and 3 weeks after the initial injury. One year after these procedures, the patient has achieved excellent functional outcomes and has returned to recreational sports.